Design of an elasticized collagen scaffold: A method to induce elasticity in a rigid protein. (15th October 2016) - Versteegden, Luuk R.; Hoogenkamp, Henk R.; Lomme, Roger M.; van Goor, Harry; Tiemessen, Dorien M.; Geutjes, Paul J.; Oosterwijk, Egbert; Feitz, Wout F.; Hafmans, Theo G.; Verdonschot, Nico; Daamen, Willeke F.; van Kuppevelt, Toin H.
Graphical abstract: Abstract: Type I collagen is widely applied as a biomaterial for tissue regeneration. In the extracellular matrix, collagen provides strength but not elasticity under large deformations, a characteristic crucial for dynamic organs and generally imparted by elastic fibers. In this study, a methodology is described to induce elastic-like characteristics in a scaffold consisting of solely type I collagen. Tubular scaffolds are prepared from collagen fibrils by a casting, molding, freezing and lyophilization process. The lyophilized constructs are compressed, corrugated and subsequently chemically crosslinked with carbodiimide in the corrugated position. This procedure induces elastic-like properties in the scaffolds that could be repeatedly stretched five times their original length for at least 1000 cycles. The induced elasticity is entropy driven and can be explained by the introduction of hydrophobic patches that are disrupted upon stretching thus increasing the hydrophobic-hydrophilic interface. The scaffolds are cytocompatible as demonstrated by fibroblast cell culture. In conclusion, a new straightforward technique is described to endow unique elastic characteristics to scaffolds prepared from type I collagen alone. Scaffolds may be useful for engineering of dynamic tissues such as blood vessels, ligaments, and lung. Statement of Significance: In this research report, a methodology is presented to introduce elasticity to biomaterials consisting of only type I collagen fibrils. The method comprises physical compression and corrugation in combination with chemical crosslinking. By introducing elasticity to collagen biomaterials, their application in regenerative medicine may be expanded to dynamic organs such as blood vessels, ligaments and lung. The combination of strength and elasticity in one single natural biomaterial may also "simplify" the design of new scaffolds.